Management Information System Through the Student Guardian Application in Islamic Boarding Schools - Luluk Sulthoniyah Luluk Sulthoniyah; Totok Sudarmanto; Zenol Rasul; Abu Bakar (IJIBS, 2026)
Advances in information technology have encouraged Islamic boarding schools to adopt Management Information Systems to improve administrative services for students' parents. This study aims to examine the planning, implementation, and evaluation of the Wali Santri application at Pondok Pesantren Fatihul Ulum Al Mahfudz Jember. A qualitative descriptive approach was employed using purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and analyzed using an interactive model with triangulation to ensure credibility. The findings indicate that system planning was based on user needs assessment and stakeholder involvement, while implementation enhanced the effectiveness, efficiency, transparency, and accessibility of administrative services through integrated digital features. Continuous evaluation enabled system improvements based on user feedback and operational needs. Overall, the Wali Santri application has improved the quality of administrative services, strengthened communication between the pesantren and students' parents, and supported more effective, technology-driven institutional management.